Perancangan Sistem Informasi Pengarsipan Customer Information File (CIF) di Bank BTN KCP Margahayu - Fauziah, Sri Tati; Aditiarno, Ratnanto; Sufyana, Candra Mecca (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Customer Information File (CIF) is information that contains customer data, both personal and institutional. The purpose of this research is to create a CIF filing information system at Bank Tabungan Negara Margahayu Sub-Branch Office. Information collection is using qualitative methods, with a descriptive approach, namely conducting observations, interviews and literature studies. The results of research that has been conducted by researchers at Bank BTN KCP Margahayu Bandung with the existence of this CIF filing information system can help better manage CIF archives to make it easier to find the existence of CIF qssuickly and precisely. Customer service will input customer data which will then check the existence of the CIF to carry out a transaction. And the output of this system is the result of checking by customer service and a CIF report to the head of the sub-branch. So it is very easy to manage CIF using this information system compared to searching and checking manually which takes a very long time and is less accurate.